Linkage Map of Escherichia coli K-12, Edition 10: The Traditional Map - Berlyn, Mary K. B. (American Society for Microbiology, 1998)
This map is an update of the edition 9 map by Berlyn et al. (M. K. B. Berlyn, K. B. Low, and K. E. Rudd, p. 1715–1902, in F. C. Neidhardt et al., ed., Escherichia coli and Salmonella: cellular and molecular biology, 2nd ed., vol. 2, 1996). It uses coordinates established by the completed sequence, expressed as 100 minutes for the entire circular map, and adds new genes discovered and established since 1996 and eliminates those shown to correspond to other known genes. The latter are included as synonyms. An alphabetical list of genes showing map location, synonyms, the protein or RNA product of the gene, phenotypes of mutants, and reference citations is provided. In addition to genes known to correspond to gene sequences, other genes, often older, that are described by phenotype and older mapping techniques and that have not been correlated with sequences are included.